When No One Notices: Disorders of Consciousness and the Chronic Vegetative State. Issue 4 (20th August 2019) - Fins, Joseph J.
Abstract: On January 5, 2019, the Associated Press reported that a woman thought to have been in the vegetative state for over a decade gave birth at a Hacienda HealthCare facility. Until she delivered, the staff at the Phoenix center had not noticed that their patient was pregnant. The patient was also misdiagnosed . Misdiagnosis of patients with disorders of consciousness in institutional settings is more the norm than the exception. Misdiagnosis is also connected to a broad and extremely significant change in the understanding of the vegetative state—a change that the field of bioethics has not yet fully taken into account. In September 2018, the American Academy of Neurology, the American College of Rehabilitation Medicine, and the National Institute on Disability, Independent Living, and Rehabilitation Research issued a comprehensive evidence‐based review on disorders of consciousness and an associated practice guideline on the care of these patients. These landmark publications update the 1994 Multi‐Society Task Force Report on the Vegetative State, which subcategorized the persistent vegetative state as either persistent (once the vegetative state lasted one month) or permanent (once the vegetative state lasted three months after anoxic injury or twelve months after traumatic injury). Noting that 20 percent of patients thought to be permanently unconscious might regain some level of consciousness, the new guideline has eliminated the permanent vegetative state as a diagnostic category, replacing it with the chronic vegetative state .